High throughput genomic and proteomic technologies in the fight against infectious diseases - Alessandro Tanca; Massimo Deligios; Maria Filippa Addis; Sergio Uzzau (Journal of Infection in Developing Countries)
New technologies have shown significant promise in the fight against infectious diseases, with the discovery of novel molecular targets for in vitro diagnostics and the improved design of vaccines. In developing countries, especially in areas of neglected diseases and resources-poor settings, a number of technological innovations are further needed, such as the integration of old and new biomarkers in suitable analysis platforms, the simplification of existing analysis systems, and the improvement of sample preservation and management. However, in these areas, identification of new biomarkers for infectious diseases is still a core issue in the diagnostic quest. Similarly, new technologies will allow scientists to design vaccines with improved immunogenicity, efficacy and safety in the local area, according to the circulating pathogenic strains and the genetic background of the population to be immunized. In this work we review the current omics-based technologies and their potential for accelerating the development of next generation vaccines and the identification of biomarkers suitable for point-of-care (POC) diagnostic applications.